Genetic Implication and Dental Consideration in Syndromes with Benign and Malignant Oral Neoplastic Component: A Narrative Review. Issue 2 (November 2019) - Singh, Saurabh; Gupta, Khushboo; Pendalya, Siva Kumar; Kondreddy, Kameswari
Background and Objective: The presence of an internal and often occult malignancy may be forewarned by various oral manifestations. Several of these findings are preferentially localized to the head and neck region, including the oral cavity. This places the dental practitioner in a unique position to detect these signs and symptoms of occult neoplastic involvement. Because they may be present before an established syndrome or cancer diagnosis, even representing the initial expression of disease in some cases, early recognition by a dentist may lead to timely diagnosis and management of these syndromes. Thus, the aim of this narrative review was literature search and gathering data of such syndromes. Materials and Methods: A Medline–PubMed search was conducted of the literature using the keywords "syndrome, " "dental management, " "Cowden's syndrome, " "Peutz–Jeghers syndrome, " "malignant component, " "Gardner's syndrome, " "Gorlin–Goltz syndrome, " and "McCune–Albright syndrome." The search strategy was limited to human studies (case reports and case series), full-text English articles published from January 1, 2000, to mid-2019. Irrelevant articles or articles with inadequate information were omitted. Results: A total of 36 pieces of literature were reviewed, of which 13 were literature reviews, 15 case reports, 3 expert committee guides and updates, and 4 original research papers, and 1 was a book. Conclusion: These syndromes pose risk during dental practice, which necessitates extra awareness and caution to prevent potential complications. Although, the multidisciplinary approach in treating these cases is not well documented, any related information may be helpful in understanding the pathogenesis and the nature of these syndromes.